COMFORT WITH ONE’S OWN HANDS: DEVELOPMENTS OF UNIVERSITY SCIENTISTS ARE INTRODUCED INTO REALITY - Vladimir P. Kozhevnikov (Высшее образование в России)
An interview with Vladimir Pavlovich Kozhevnikov, a department head, candidate of technical sciences, professor at Belgorod State Technological University named after V.G.Shukhov, touches upon innovative developments of BSTU scientists, who have created the university system of autonomous heat supply. The paper presents the work of a training research and production complex at BSTU providing scientific and methodological assistance in students training within the program of «heat and power supply». The paper contains a block diagram for enhancing energy management system at BSTU.